Study of AC-DC converter - Masud, Ali Tanjim Bin; Kabir, Md. Ishmam; Zannat, Meftahul; Banik, Niloy (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.